Greenhouse Gas Emissions and Health Outcomes in Nigeria: Empirical Insight from Auto-regressive Distribution Lag Technique - Matthew, Oluwatoyin; Osabohien, Romanus; Fagbeminiyi, Fasina; Fasina, Afolake (International Journal of Energy Economics and Policy, 2018)
This study examines the long-run effect of emissions of greenhouse gas on health outcomes in Nigeria using time series data from 1985-2016 engaging the Auto-regressive Distribution Lag (ARDL) econometric approach to cointegration and it was observed that human activities increase greenhouse gases to the atmosphere, this is through combustion of fossil fuels and CO2, these are two major sources of Greenhouse gas Emissions. When the quantity of carbon dioxide increases in the air, more heat is stored in the atmosphere; and this comes upon human beings thereby causing a great harmful effect to human health. The result from ARDL econometric approach to cointegration shows that 1 percent increase in greenhouse gas emissions reduces life expectancy by 0.0422 percent which is used as a proxy for health outcome, if this happens, invariably, mortality rate will be 146.6 percent. Therefore, the major strategy among others recommended in this study for controlling gaseous emissions and increase life expectancy is public health expenditure as the results also shows that 1 percent increase in government health care expenditure increases life expectancy approximately by 18.10 percent. Keywords: Greenhouse Gas Emissions, CO2, Health outcomes, ARDL JEL Classifications: Q4; H51; B4